The Effect of Adherence to Antihypertensive Therapy and Cardiovascular Risk Among Hypertensive Patients in Purworejo Regency - Prili Arwinda; Dita Maria Virginia; Phebe Hendra (Sanata Dharma University, 2024)
Uncontrolled hypertension will increase mortality and morbidity rates. The adherence is an important factor in controlling blood pressure. Uncontrolled blood pressure will affect cardiovascular risk. Therefore, hypertensive patients must comply with taking medication to control blood pressure and cardiovascular risk. This study was an analytical observational study with a cross-sectional design. A total of 85 respondents who met the inclusion criteria were measured for adherence using the MPR (Medication Possession Ratio) method and the MARS-5 (Medication Adherence Report Scale-5) questionnaire. A patient who had blood pressure 140/90 mmHg was categorized as controlled hypertension. The cardiovascular risk was measured using the ACC/AHA criteria method. Data were analyzed using chi-square tests and odds ratio (OR) with 95% confidence interval (CI) and p0.05 considered significant. This study showed that there was a significant association between adherence to antihypertensive therapy to controlled blood pressure, either according to MPR (OR=18.262; 95%CI=5.259-63.412; p=0.000) and MARS-5 (OR=31.607; 95%CI=8.170-122.277; p=0.000). A significant association was found between antihypertensive adherence and cardiovascular risk, either according to MPR (OR=3.733; 95%CI=1.269-10.983; p=0.020) and MARS-5 (OR=9.000; 95%CI=2.702-29.983; p=0.000). Therefore, this study concludes a significant relationship between antihypertensive adherence to controlled blood pressure and cardiovascular risk in Purworejo Regency.